Dupilumab in daily practice for the treatment of pediatric atopic dermatitis: 28‐week clinical and biomarker results from the BioDay registry. Issue 12 (5th December 2022) - Kamphuis, Esmé; Boesjes, Celeste M.; Loman, Laura; Bakker, Daphne S.; Poelhekken, Mila; Zuithoff, Nicolaas P. A.; Kamsteeg, Marijke; Romeijn, Geertruida L. E.; van Wijk, Femke; de Bruin‐Weller, Marjolein S.; de Graaf, Marlies; Schuttelaar, Marie L. A.
Abstract: Background: Dupilumab has proven to be an effective and safe treatment for atopic dermatitis (AD) in pediatric patients in clinical trials. However, few daily practice studies are available. The aim of this study is to evaluate the effect of 28 weeks dupilumab treatment on effectiveness, safety, and serum biomarkers in pediatric patients with moderate‐to‐severe AD in daily practice. Methods: Patients visited the outpatient clinic at baseline, 4, 16, and 28 weeks of treatment. Disease severity was assessed by the Eczema Area and Severity Index (EASI), Investigator Global Assessment (IGA), Numeric Rating Scale (NRS)‐pruritus and ‐pain, and the Patient‐Oriented Eczema Measure (POEM). Side effects were evaluated. Nineteen severity‐associated serum biomarkers were measured. Predicted‐EASI (p‐EASI) was calculated. Results: Sixty‐one patients were included. Respectively 75.4%, 49.2%, and 24.6% reached EASI‐50, EASI‐75, and EASI‐90 and 36.1% achieved an IGA‐score (almost) clear. Improvement of ≥4 points on POEM, NRS‐pruritus, and NRS‐pain was reached by 84.7%, 45.3%, and 77.4%, respectively. Most reported side effects were conjunctivitis ( n = 10) and headache ( n = 4). Biomarkers TARC, PARC, periostin, sIL‐2Ra, and eotaxin‐3 significantly decreased during treatment. The p‐EASI showed a significant correlation with disease severity. Conclusion: Dupilumab treatment significantly improved disease severity and disease‐associated symptoms and decreased severity‐associated serum biomarkers in pediatric AD patients in daily practice.